2022
DOI: 10.1155/2022/1790826
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization of Flash Extraction of Akebia trifoliata Seed Oil by the Box-Behnken Response Surface Methodology and Comparison of Oil Yields from Different Origins

Abstract: The aim was to optimize the extraction process of Akebia trifoliata seed oil. Using Akebia trifoliata seed as raw material, the oil extraction rate was used as index. The effect of flash extraction on the yield of Akebia trifoliata seed oil was investigated. Taking the liquid-material ratio, extraction voltage, and extraction time as the investigation factors and the oil extraction rate of Akebia trifoliata seed as the response value and on the basis of the single-factor test, the extraction process of Akebia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…A BBD [ 30 , 31 ] was applied to evaluate the significant effects of the factors, magnetron voltage (X1), extraction time (X2), and pH of the extraction medium (X3), on the yield of azadirachtin obtained. Table 1 shows the range of the independent variables and their levels.…”
Section: Methodsmentioning
confidence: 99%
“…A BBD [ 30 , 31 ] was applied to evaluate the significant effects of the factors, magnetron voltage (X1), extraction time (X2), and pH of the extraction medium (X3), on the yield of azadirachtin obtained. Table 1 shows the range of the independent variables and their levels.…”
Section: Methodsmentioning
confidence: 99%
“…Liu Xianglin et al systematically reviewed and explored the plant propagation technology of fruit-type A. trifoliata . Guo Linxin et al isolated and identified the chemical constituents of A. trifoliata, and tested its antioxidant activity to lay a foundation for the research on the medicinal substances and related mechanisms of A. trifoliata (Guo et al, 2017).Huang Rongrong et al investigated the effect of flash extraction on the yield of A. trifoliata seed oil (Huang et al, 2022). Jiang Yongli et al explored the effects of cell-wall metabolism on A. trifoliata fruit cracking (Jiang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…isolated and identified the chemical constituents of A. trifoliata , and tested its antioxidant activity to lay a foundation for the research on the medicinal substances and related mechanisms of A. trifoliata ( Guo et al., 2017 ).Huang Rongrong et al. investigated the effect of flash extraction on the yield of A. trifoliata seed oil ( Huang et al., 2022 ). Jiang Yongli et al.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%